STRATEGI MEMPERTAHANKAN KEARIFAN LOKAL DALAM BUDIDAYA PADI DI DESA SIMPANG RAYA KECAMATAN PANEI KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Sidabutar, Okta Silvia; Sayamar, Eri; Kausar, Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Commodities rice (Oryza sativa L.) is one class of Gramineae plants or grasses suitable to be developed in Indonesia. Simpang Raya originated from Simpang Raya legalization in 1918 which previously was the village Parsaguan Kalapa. The village originally planted sago as their staple food ,. But when the Dutch colonial war, the invaders (the Netherlands) to bring rice seed to work with communities in paddy fields. It survived until now. Community Simpang Raya almost all rice farming not only for their own consumption, but also sold to the agents of rice in the village. Simpang Raya also own and maintain local knowledge to society. local wisdom that thrive in everyday life either through direct teaching from parents to children and from ompung to pahompu (grandchildren). Simpang Raya community life is very thick with ancestral traditions. One example of local wisdom that they do rice farmers till today as land clearing, the clearing process farmers implement partamiangan (intercession) before clearing that aims to always remember and rely on God in every step as well as in carrying out rice cultivation. This study using interviews, questionnaires and Snowball Sampling in the number of respondents the right to obtain 7 respondents consisting of 1) village officials, 2) traditional figure, 3) Farmers Rice. In a number of local wisdom do rice farmers then and now at 39 local wisdom. Keyword: local wisdom, paddy plant, strategy local wisdom